The Impact of Conservation Information on Average Abnormal Return: Time Series Analysis - Murwatiningsih Murwatiningsih; Arief Yulianto; Kris Brantas Abiprayu; Andhi Wijayanto (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2018)
The aims of this research are to examine the impact of conservation-based information to average abnormal return of firms. The data which used in this research are all of the news regarding corporate action especially conservation-based information that gathered from Bisnis Indonesia from July 2016 through August 2017. All of the firm which also listed in Sri Kehati Index. The order of the examination within this research are (1) stationery test (2) ARCH or GARCH test (3) Dummy test (Least Square Dummy Variable) and (4) Hypothesis test). The results show that the change in AAR is not influenced by conservation publication made by Bisnis Indonesia. It means that the average AAR difference occurs only in the sample yet the result cannot be generalized in capital market in Indonesia.